Foreign Languages in the System of Continuing Education (Experience in Development and Implementation of the Author’s Model) - Khilkovska , A. (New Collegium, 2021)
The paper covers the history of Foreign Languages Department of People’s Ukrainian Academy, whose aim is to provide language training to “Business Administration” and “Social Management” students, paying special attention to the main stages developing its approach to organization and teaching methods has gone through. One of the major steps on this way was the development of the “Integrated Programme of Continuing English Language Training in PUA” which formalized the department’s main principles of organizational and teaching activities: competence-based approach, interactive teaching/learning methods, as well as digital ones, authentic teaching/learning materials, streaming, Grammar and Speaking classes, which is not common for non-philological departments. The paper explicates the way competence-based approach entails transformation of in-class language teaching/learning, as well as students’ extra-curricular activity. The author makes the conclusion that most practices, principles and approaches seen as experimental at early stages, later have formed the basis of language teaching/learning in PUA, moreover, some of them have already been implemented on the national level in response to formal requirements of the Ukrainian Ministry of Education and Science.